PENERAPAN MEDIA WORDWALL UNTUK MENINGKATKAN HASIL BELAJAR PADA MATA PELAJARAN BAHASA INDONESIA KELAS V SEKOLAH DASAR - Dwi Apriyani; Erna Labudasari; Ade Nurningsih (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
This Classroom Action Research (CAR) aims to improve learning outcomes through the application of Wordwall media in the Indonesian language subject for Grade V of elementary school. The research was conducted at SDN 2 Watubelah during the even semester of the 2024/2025 academic year over two cycles, each consisting of one meeting. Each cycle included four stages: planning, implementation, observation, and reflection. In this action, Wordwall media was used in the learning process. Data was collected through students’ learning outcomes.The results from the pre-cycle, Cycle I, and Cycle II showed a significant improvement in both the learning process and students' learning outcomes. Before the action was taken, in the pre-cycle, the percentage of students meeting the minimum mastery criteria was 52%. After the implementation of Wordwall media, in Cycle I, the percentage increased to 63%, and in Cycle II, it rose significantly to 89%.This improvement indicates that Wordwall media is effective in enhancing students' learning outcomes. In conclusion, the implementation of Wordwall media in Grade V at SDN 2 Watubelah successfully improved students’ learning outcomes significantly, as shown by the data from each cycle.